Robots for minimally invasive diagnosis and intervention - Huda, Nazmul; Yu, Hongnian; Cang, Shuang (Elsevier, 2016)
Minimally invasive diagnosis and interventions provide many benefits such as higher efficiency, safer, minimum pain, quick recovery etc. over conventional way for many procedures. Large robots such as da-Vinci are being used in this purpose, whereas research of miniature robots for laparoscopic and endoscopic use, is growing in the recent years. A comprehensive literature search is performed using keywords’ laparoscopic robot, capsule endoscope, surgical medical robot etc. primarily for the time period of 2000–2015. The articles relevant to the theme of the paper are reviewed and included in the paper. This paper concentrates medical robots for minimally invasive diagnosis and intervention in general and propulsions of miniature robots in particular. Robots are classified and compared using critical characteristics and summarized in Table 1, Table 2, Table 3, Table 4, Table 5 and Table 6. Large robots such as da-Vinci are successfully used in many procedures e.g. neurosurgery, cardiothoracic surgery etc. However there are needs for more functionality which might lead to flexible robots. For miniature robots, each propulsion mechanism has some advantages and disadvantages. While external magnetic propulsions have potential to provide propulsion without increasing the robot size, they lack precise position control and may require expensive and bulky equipment. On the other hand internal propulsions have the capability of precise position control but require mechanisms which need substantial amount of power to drive. Hybrid propulsion which combines best features of both internal and external propulsions could be a solution for this. Robots have improved the healthcare services for many medical procedures. However, still there are challenges to address to enable use of medical robots universally inside and outside hospitals for diagnosis and interventions.
Keywords: Medical robot; Capsule endoscopy; Laparoscopic surgery; Propulsion mechanism; In vivo miniature robot; Minimally invasive surgery